Analysis of the structure and location of charcoal production in Brazil - time period from 1980 to 2007 - Thais Carvalho; Carlos Bacha (European Regional Science Association (ERSA), 2010)
This paper aims to analyze the regional impacts of the steel and environmental policies on the structure and location of charcoal production in Brazil during the time period from 1980 to 2007. Both statistic and interpretative analysis of secondary data, organized in tables or graphs, are used, paying a special attention to the similarities and differences among the database. The main findings of the paper are: (1st) even though charcoal is an archaic energy source, it still represents 3% of the Brazilian energetic matrix and is rather used in the industrial sector, especially in the steel industry, in which there are steelmakers that use coal (to produce flat steel) or charcoal (if they produce long steel); (2nd) charcoal production trend is directly associated to its industrial use (the correlation coefficient between these two variables is 0.986 in time period from 1980 to 2007); (3rd) due to the impacts of industrial and environmental government policies, charcoal production in the Northern and Northeastern Brazil are mainly conducted by small producers making use of native forests; (4th) also in Northern and Northeastern Brazil, independent producers of pig iron are predominating (exporting most of their production) as well as the environmental legislation enforcement is weaker in relation to other Brazilian regions; (5th) otherwise, largest producers, using mostly planted forests, are predominating in Southeastern Brazil, where environmental law enforcement is stronger and where both integrated steelmakers based on charcoal or on coal are present; (6th) the concentration of charcoal production has increased in Brazil, however the inequality among the producers has decreased. The largest producers (with 10,000 or more hectares) accounted for 8.4% of Brazilian charcoal production in 1980 and for 15.6% in 1996, despite the Gini coefficient among charcoal producers has reduced from 0.793 to 0.757 in the same years, respectively. (7th) Regional differences in relation to inequality and concentration of charcoal production among Brazilian regions have taken place and they are specified and analyzed in the paper. By the end, the papers suggest some policies to improve charcoal production in Brazil with more balance in relation to regional distribution.
Keywords: 330; Charcoal; Steel Sector; Regional Differences; Brazil